Profil Teamwork Skill sebagai Gambaran Kemampuan Kompetitif Mahasiswa - Ichda Chayati; Sutriyati Purwanti; Mutiara Nugraheni (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of the study were: 1) to identify the profile of the Hospitality Engineering Education students’ teamwork skills, 2) to identify the profile of the Hospitality Engineering Students’ teamwork skills, 3) to describe the general overview of the students’ teamwork skills, 4) to identify the group of Bachelor program with the highest and the lowest teamwork skills, 5) to identify the group of the Associate program with the highest and the lowest teamwork skills. This study was a descriptive study. The results showed: 1) the Hospitality Engineering Education students who were at the stages of forming, storming, norming, and performing teamwork skills were 1.02%; 0.52%; 53.39%; and 45.07% respectively, 2) The Hospitality Engineering students who were at the stage of forming, storming, norming, and performing teamwork skills were 2.3%; 2.43%; 54.85%; and 40.42% respectively, 3) All of students in Bachelor and Associate programs generally have good team work skills, 4) in the Bachelor level, the groups with the highest teamwork skills were the regular Bachelor program of 2011 and the non-regular Bachelor program of 2010, while the groups with the lowest teamwork skills were the regular Bachelor program of 2009 and the non-regular Bachelor program of 2009, 5) at the Associate level, the group with the highest teamwork skills was the regular Associate program of 2011, while the group with the lowest team work skills was the regular Associate program  of 2010.